Impact of smartphone application 'Dent-O-Xpert' on oral health related knowledge, attitude and behavior of young adults - A randomized control trial - Sandesh Nagarajappa; Chirag Vyas; Prashant Mishra; Dhaman Gupta; Thippeswamy HM; Shantanu Sontakke (Elsevier, 2023)
Background: Maintaining optimal oral health requires a combination of knowledge, awareness, and consistent behavioral practices. Smartphone technology has revolutionized various aspects of modern life, including healthcare. The widespread smartphone usage in India offers an opportunity to study its positive influence on oral health behaviors. Aim: to assess the impact of smartphone application "Dent-O-Xpert" on oral health-related knowledge, attitude, and behavior among young adults. Methods: The randomized double-blind controlled trial involved 168 young adults aged 18-25 from professional institutions in Indore, India. The intervention group received oral health education through "Dent-O-Xpert" smartphone application with educational content, interactive modules, reminders and personalized recommendations, while the control group received traditional oral health sessions. Primary outcome measure including knowledge, attitude, behavior, and oral hygiene were evaluated through validated questionnaires and clinical examinations at baseline, 1 month, and 2 months. The data were analyzed using SPSS-23. Results: The Dent-O-Xpert group showed significantly improved oral health knowledge scores at both follow-ups. By second follow-up visit, both plaque and oral hygiene scores were significantly reduced in Dent-O-Xpert group (0.25 ± 0.4) compared to control group (0.71 ± 0.48). Tooth-brushing frequency (96.4 %), brushing techniques (59.5 %), timely toothbrush changes (97.6 %), and use of supplementary oral hygiene aids (31-35.7 %) improved in the Dent-O-Xpert group. Attitudes toward oral health care were also more positive in this group. No significant changes in oral health behavior and attitude were observed in the control group. Conclusion: the study findings indicate that Dent-O-Xpert smartphone application is effective in improving the oral health related knowledge, attitude and behavior.